Evaluation of long-term effectiveness of the use of carglumic acid in patients with propionic acidemia (PA) or methylmalonic acidemia (MMA): study protocol for a randomized controlled trial - Marwan Nashabat; Abdulrahman Obaid; Fuad Al Mutairi; Mohammed Saleh; Mohammed Elamin; Hind Ahmed; Faroug Ababneh; Wafaa Eyaid; Abdulrahman Alswaid; Lina Alohali; Eissa Faqeih; Majed Aljeraisy; et al. (BMC, 2019)
Abstract Introduction Propionic acidemia (PA) and methylmalonic acidemia (MMA) are rare autosomal recessive inborn errors of metabolism characterized by hyperammonemia due to N-acetylglutamate synthase (NAGS) dysfunction. Carglumic acid (Carbaglu®; Orphan Europe Ltd.) is approved by the US Food and Drug Administration (USFDA) for the treatment of hyperammonemia due hepatic NAGS deficiency. Here we report the rationale and design of a phase IIIb trial that is aimed at determining the long-term efficacy and safety of carglumic acid in the management of PA and MMA. Methods This prospective, multicenter, open-label, randomized, parallel group phase IIIb study will be conducted in Saudi Arabia. Patients with PA or MMA (≤15 years of age) will be randomized 1:1 to receive twice daily carglumic acid (50 mg/kg/day) plus standard therapy (protein-restricted diet, L-carnitine, and metronidazole) or standard therapy alone for a 2-year treatment period. The primary efficacy outcome is the number of emergency room visits due to hyperammonemia. Safety will be assessed throughout the study and during the 1 month follow-up period after the study. Discussion Current guidelines recommend conservative medical treatment as the main strategy for the management of PA and MMA. Although retrospective studies have suggested that long-term carglumic acid may be beneficial in the management of PA and MMA, current literature lacks evidence for this indication. This clinical trial will determine the long-term safety and efficacy of carglumic acid in the management of PA and MMA. Trial registration King Abdullah International Medical Research Center (KAIMRC): (RC13/116) 09/1/2014. Saudi Food and Drug Authority (SFDA) (33066) 08/14/2014. ClinicalTrials.gov (identifier: NCT02426775) 04/22/2015.